Economic Implications of Terrorism in Northern Nigeria - Philip Oche Musa; Adebola Alade; Mohammed Adamu (Universitas Medan Area, 2026)
Terrorism is one of the major challenges governments around the world have been tackling since 2000. Despite efforts to deal with the challenges, there has been a rise in terrorist activities, particularly of Islamic extremist groups. The purpose of the study investigated the major causes of terrorism in Northern Nigeria and the economic implications in the country. The research method is both qualitative and quantitative research approach. The paper explores the use of questionnaires and interviews to collect data from respondents in selected local government areas of Borno, Katsina, and Zamfara States. The study employed descriptive statistics method for data analysis. The findings from the study revealed that the major cause of terrorism in northern Nigeria is the emergence of the Boko haram sect in the North-Eastern part of Nigeria, which led to the loss of thousands of lives and mass destruction of properties in the affected areas. Other major causes of terrorism are the influx of illegal aliens into the country, extreme poverty, and a high rate of illiteracy in the Northern part of Nigeria. The study also revealed that the major economic implications of terrorism in North-Western Nigeria are mass destruction of public markets, declining foreign direct investment, increased budget on security, food shortage, and declining business activities in the affected areas. On this note, the study recommended that the government should re-strategise not only on military intervention to combat all acts of terrorism across the country, but also on improving infrastructure to support human capital development, business growth, and employment generation.